Решение.
Применяем формулы разности квадратов, квадрата суммы, квадрата разности .
[tex]\displaystyle \bf \Big(\frac{a+b}{a-b}+\frac{a-b}{a+b}\Big)\cdot \frac{a^2-b^2}{a^2+b^2}=\frac{(a+b)^2+(a-b)^2}{(a-b)(a+b)}\cdot \frac{a^2-b^2}{a^2+b^2}=\\\\\\=\frac{a^2+2ab+b^2+(a^2-2ab+b^2)}{a^2-b^2}\cdot \frac{a^2- b^2}{a^2+b^2}=\frac{2(a^2+b^2)}{a^2+b^2}=2[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Решение.
Применяем формулы разности квадратов, квадрата суммы, квадрата разности .
[tex]\displaystyle \bf \Big(\frac{a+b}{a-b}+\frac{a-b}{a+b}\Big)\cdot \frac{a^2-b^2}{a^2+b^2}=\frac{(a+b)^2+(a-b)^2}{(a-b)(a+b)}\cdot \frac{a^2-b^2}{a^2+b^2}=\\\\\\=\frac{a^2+2ab+b^2+(a^2-2ab+b^2)}{a^2-b^2}\cdot \frac{a^2- b^2}{a^2+b^2}=\frac{2(a^2+b^2)}{a^2+b^2}=2[/tex]